The Effect Of The Cooperative Integrated Reading And Composition Model Assisted Video Media On Reading Comprehension And Critical Thinking - Ahmad, Arifin; Musthafa, Bachrudin; Sunendar, Dadang; Septian, Ryan (PrimaryEdu : Journal of Primary Education, 2023)
The purpose of this study is to find out the Cooperative Integrated Reading And Composition model assisted by video media on its effect on reading comprehension and critical thinking. With a hypothesis that has a significant effect on students' reading comprehension and critical thinking skills, this research departs from the low reading comprehension ability and critical thinking skills of students at SDN Cihanjawar 02. A quantitative method with a quasi-experimental method is the method used in this research. Meanwhile, the design used is a non-equivalent group by conducting a pretest and posttest. Management techniques are carried out using normality tests, homogeneity tests, t tests and effect sizes. With the results of this research data analysis, there is an influence arising from the use of the Cooperative Integrated Reading And Composition model on the ability to read comprehension and critical thinking of fifth grade students at SDN Cihanjawar 02 based on the results of the Independent Sample T test obtained a sig (2-taled) value of 0.025 < 0.05 for reading comprehension ability and 0.010 <0.05 which means H0 is rejected and Ha is accepted. With the influence seen from the effect size test of 0.54 for reading comprehension skills and 0.60 for critical thinking skills, it can be said that the Cooperative Integrated Reading And Compositon model assisted by video media has a moderate effect. Keywords: CIRC, Reading Comprehension, Critical Thinking